Anterior cervical discectomy and fusion using polyetheretherketone (PEEK) cage - Jha, Rajiv (Nepal Journal of Neuroscience, 2021)
Introduction:There are ways to operate for herniated cervical disc starting from simple discectomy to artificial disc replacement. Materials and Methods:This is a prospective study of anterior cervical discectomy and fusion with polyetheretherketone (PEEK) age device conducted from January 2016 till September 2019. Age, sex ratio, the level of disc prolapses, symptoms, complications of surgery and the outcome was assessed.Neurological assessment was done pre-and postoperative as defined by Odom’s criteria and Ranawat et al grading system. Check x ray was done at 3 and 6 months. Results: The total number of cases was 82, predominantly males (62%). Disc prolapse due to degenerative disease was the most common case (68%). C5-6 was the most often disc prolapse level (40%), followed by C6-7 level (38%) with multiple level disc prolapse in 12%. Applying Ranawat grading system of neurological deficit; at presentation, majority were in Grade II (54%), followed by Grade IIIA (19%). Postoperatively there was a reduction in weakness from 54% to 16% in Grade II and from 19% to 8% for Grade IIIA. Majority had excellent and good outcome based on Odom’s criteria. The continuity of the graft and the adjacent spinal curvature was also assessed and there was more than 96% fusion rate. Conclusion:Use of local autograft with a PEEK cage hasbenefit of working within the same operative window as the ACDF, thus reducing the infection, bleeding, and pain risks that may be encountered with a second incision. It is very safe to use in single level or multilevel cervical disc prolapse and also saves additional time of harvesting graft from donor site.